2020
DOI: 10.1021/acs.molpharmaceut.0c00737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrophobic Tail Length Variation on Surfactant-Mediated Protein Stabilization

Abstract: Recently, protein therapeutics have gained significant attention as a result of their enhanced selectivity and diminished side effects compared to traditional small-molecule drugs. Despite their advantages, protein formulations typically suffer from stability issues because of aggregation and denaturation during production and storage, often resulting in detrimental immune responses. Surfactants can be used to stabilize and protect proteins in solution by preventing protein adsorption onto interfaces or by for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
(95 reference statements)
1
14
0
Order By: Relevance
“…For the other surfactants, CMC results showed that the longer the alkyl chain, the lower the CMC, increasing from 0.07 mM for C 16 TreSuc to 0.96 mM for C 10 TreSuc . This is in good agreement with results obtained with other surfactants ( Hanson et al, 2020 ). More interestingly, other groups have studied the CMC of non-succinylated trehalose monoalkyl derivatives ( Chen et al, 2007 ).…”
Section: Resultssupporting
confidence: 93%
“…For the other surfactants, CMC results showed that the longer the alkyl chain, the lower the CMC, increasing from 0.07 mM for C 16 TreSuc to 0.96 mM for C 10 TreSuc . This is in good agreement with results obtained with other surfactants ( Hanson et al, 2020 ). More interestingly, other groups have studied the CMC of non-succinylated trehalose monoalkyl derivatives ( Chen et al, 2007 ).…”
Section: Resultssupporting
confidence: 93%
“…Polymer excipients are inactive ingredients included in pill formulations that are frequently, but not exclusively, used to sequester small molecules and larger payloads through noncovalent interactions with active pharmaceutical ingredients (APIs), , proteins, and polynucelotides . In oral, intravenous, or intramuscular administration, the polymer works with the active ingredients as a stabilizer, both on the shelf and in vivo.…”
mentioning
confidence: 99%
“…The CMC value of FM1000 is slightly different than that reported by Hanson et al (denoted as 14FM1000), where dynamic light scattering was used to measure the CMC of FM1000 in 0.9% saline. We believe this difference is due to the different solution matrices and techniques used in this study …”
Section: Results and Discussionmentioning
confidence: 95%
“…We believe this difference is due to the different solution matrices and techniques used in this study. 43 Our earlier study reported a CMC of 1.6 × 10 −2 mg/mL (12 μM) for PS80, 45 and PS80's CMC value is approximately five times higher than the CMC value for FM1000, indicating that a lower concentration of FM1000 would be sufficient to form a surfactant monolayer onto the surface. Additionally, a Langmuir adsorption fit to the constructed equilibrium surface tension as a function of bulk concentration indicated a maximum packing of surfactant concentration (Γ ∞ ) of around 1.88 mg/m 2 for PS80 and 1.45 mg/m 2 for FM1000.…”
Section: ■ Methodsmentioning
confidence: 87%
See 1 more Smart Citation